Dissemination of the Scientific Ideas of Professor Bronislovas Bitinas in the Science of Education - Barkauskaitė, Marijona (Pedagogika, 2016)
Volume 124 of the journal of research papers “Pedagogy Studies” of 2016 is dedicated to the 90th anniversary of Professor Habilitated Doctor Bronislovas Bitinas and the 65th anniversary of his active pedagogical and scientific activity. The theoretical and practical significance of the problems, ideas and statements provided by the authors of the presented scientific articles, as well as their applicability in the interdisciplinary environment are unified not only by the analysis of the issues of education and personal development, but also by the dissemination of the fundamental scholarly works of the prominent researcher B. Bitinas in the education process, which is implemented by his students and colleagues that are guided by the Professor’s ideas and spread them in different Lithuanian universities and education institutions. The aim of the current Epilogue is to identify and discuss the main areas of the research work of Professor B. Bitinas: “Philosophy of Education.Education Ideas and Issues”, “Educational Research: the System and Process”, “Hodegetics: Theory and Technology of Upbringing”, and “Education Terminology: Quality and Issues”. According to B. Bitinas, the selected and discussed activity areas, as well as research insights should be related to a specific stage of the reform of education system revealing the possibilities of its continuation, validating its necessity by specific studies and the latest documents, seeking to improve the process of education by sharing experience, discovering in-depth connections among representatives, theoreticians and practitioners of different sciences, education systems, cultures and others. In this regard, the professionalism and distinctiveness of Professor B. Bitinas are underlined by the dissemination of his ideas and their recognition within the global context of science.